BRICS Policy Agenda, Partnership and Cooperation - Siphamandla Zondi (Journal of BRICS Studies, 2024)
In 2024, the BRICS diplomacy under the chairship of Russia is focused on partnership and cooperation in three key tracks - politics and security, the economy and finance, and cultural and humanitarian ties. Through some 250 events and meetings culminating in the BRICS Summit in Kazan in 22-24 October, the BRICS hopes to expand the range of activities it must undertake to make advances practically in policy areas in these three tracks. This year also marks the full participation of the five new members of BRICS (Egypt, Ethiopia, Iran, Saudi Arabia and United Arab Emirates) in the whole year of discussion leading the summit and the content of the declaration to be adopted about what steps the BRICS countries agree to undertaken to implement their decisions. The developments of the year can be viewed on the website: https://brics-russia2024.ru/en/.